Pengaruh Inflasi, PDRB, Dan Konsumsi Rumah Tangga Terhadap Tingkat Kemiskinan Di Indonesia Periode 2019-2022 - Salsadilla Sherly Rosalyne; Sindy Bashirotul Hidayah; Anita Ziadatul Khoiroh; Catur Restu Wijaya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The Central Statistics Agency explains that poverty is the inability to meet minimum standards of needs, both food and non-food needs. According to BPS, poverty is the condition of a person who is only able to meet his food needs of less than 2100 calories per capita per day. This research aims to determine the influence of inflation, GRDP and household consumption on poverty levels in Indonesia for the 2019-2022 period. The data used in this research is secondary data in the form of monthly time series data for four years, namely 2019-2022 with a sample size of 48. The analytical method used is a quantitative method with multiple linear regression analysis. Based on the results of the T test analysis, it was found that the variables Inflation, GRDP and Household Consumption partially influence poverty in Indonesia. Then an F test was carried out which showed that the variables Inflation, GRDP and Household Consumption simultaneously had a significant effect on poverty in Indonesia. This determination produces a determination (R2) of 0.959. Shows that the contribution of the variables Inflation, GRDP and Household Consumption to Poverty in Indonesia is 95.9%. Meanwhile, the remaining 4.1% is explained by other variables not included in this study.